An in-depth examination of electric vehicle incentives: Consumer heterogeneity and changing response over time. (February 2020) - Jenn, Alan; Lee, Jae Hyun; Hardman, Scott; Tal, Gil
Abstract: We investigate the impacts of a combination of incentives on the purchase decision of electric vehicle buyers in California from 2010 through 2017. We employ a comprehensive survey on over 14, 000 purchasers of electric vehicles in the state of California. The survey covers a swath of purchase intentions, general demographics, and importance of various incentives. Our results indicate that the most important incentives for plug-in electric vehicle (PEV) owners are the federal tax credit, the California state rebate, and high occupancy vehicle (HOV) lane access. In addition, the importance of the incentives and their associated effect on purchase behavior has been changing over time: respondents are less likely to not change their decision and more likely to not buy a vehicle at all as time passes and the technology moves away from early adopters. Incentives are becoming more important for vehicle adopters as PEV market entry progresses.